2009
DOI: 10.1096/fj.09-129445
|View full text |Cite
|
Sign up to set email alerts
|

The influence of macrophage migration inhibitory factor gene polymorphisms on outcome from community‐acquired pneumonia

Abstract: The cytokine, macrophage migration inhibitory factor (MIF), is encoded in a functionally polymorphic locus and subjects with high-expression MIF alleles are at an increased risk of inflammatory disease. Severe sepsis is the leading cause of death in intensive care units, and the prevailing hypothesis is that an excessive innate response contributes to its pathogenesis. To assess if MIF alleles influence the clinical course of infection, we conducted a case-control study to assess susceptibility and a parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 47 publications
5
71
1
3
Order By: Relevance
“…with severe sepsis (31), and with survival in patients with community-acquired pneumonia (32). Carriage of the low-expression MIF allele (CATT 5 ) protected children from meningococcemia (33), but it predisposed older adults to Gram-negative bacteremia (34).…”
Section: Discussionmentioning
confidence: 99%
“…with severe sepsis (31), and with survival in patients with community-acquired pneumonia (32). Carriage of the low-expression MIF allele (CATT 5 ) protected children from meningococcemia (33), but it predisposed older adults to Gram-negative bacteremia (34).…”
Section: Discussionmentioning
confidence: 99%
“…Control sera were obtained from 143 disease-free subjects with similar demographics enrolled in the Genetic and Inflammatory Markers of Sepsis Study (30). Serum MIF levels were measured by sandwich ELISA using specific antibodies (27).…”
Section: Methodsmentioning
confidence: 99%
“…In infectious diseases, there are reported associations between high-expression MIF alleles and improved outcomes in outpatient pneumonia and meningococcal meningitis, but more severe malaria (29)(30)(31). Analogous to the role of MIF defined in mouse models, it seems that the influence of MIF on the severity of infectious diseases (exacerbation or protection) depends on the particular pathogen or disease pathology.…”
Section: Significancementioning
confidence: 99%
“…Genetic variations consistent with low MIF expression are associated with increased risk for community-acquired pneumonia and recent studies have demonstrated that Mif-knockout mice have increased Streptococcus pneumoniae nasal carriage and decreased clearance of these bacteria (34,158). MIF is critical for the transcription of the pattern recognition receptor dectin-1, which is important for mediating clearance of Mycobacterium tuberculosis (33).…”
Section: Mif In Animal Models and Human Studies Of Age-related Lung Dmentioning
confidence: 99%